Effect of Pre-Oxidation on a Ti PVD Coated Ferritic Steel Substrate during High-Temperature Aging - Maria-Rosa Ardigo-Besnard; Aurélien Besnard; Galy Nkou Bouala; Pascal Boulet; Yoann Pinot; Quentin Ostorero (Crystals, 2022)
A PVD coating is often applied on the surface of metallic alloys to improve their high-temperature resistance. In the present work, a thin titanium layer (1.2 µm) was deposited by PVD on the surface of a stainless steel substrate before high-temperature exposure (800 °C in ambient air). The underlying idea is that metallic Ti converts into Ti oxide (TiO2) during high-temperature aging at 800 °C, thereby slowing down the substrate oxidation. The stability of the coating with and without substrate pre-oxidation was investigated. Morphological, structural, and chemical characterizations were performed and completed by simulation of the film growth and measurement of the mechanical state of the film and the substrate. In the case of the sample that was not pre-oxidized, the oxidation of the steel was slowed down by the TiO2 scale but spallation was observed. On the other hand, when the steel was pre-oxidized, TiO2 provided more significant protection against high-temperature oxidation, and spalling or cracking did not occur. A combination of different kinds of stress could explain the two different behaviors, namely, the mechanical state of the film and the substrate before oxidation, the growing stress, and the thermal stress occurring during cooling down.